Dampak Realokasi Subsidi Pupuk Menjadi Subsidi Harga Pembelian Pemerintah (Hpp) Gabah Terhadap Pendapatan Petani - Akhmad Riyadi Wastra; Ahmad Dalhar (Program Studi Agribisnis UIN Syarif Hidayatullah Jakarta, 2021)
Nowadays, the fertilizer subsidy program is less effective indicated by the scarcity of supply and the soaring price of fertilizer at the farmer level. In this condition, the government, DPR, and the public are relatively dissatisfied with the current subsidy policy, so that it becomes a discourse to change the fertilizer subsidy mode that is direct to producers into subsidies that are directly applied to farmers. It must be realized that subsidies applied to producers as well as direct subsidies to farmers will have advantages and disadvantages based on the factors that influence them. Therefore, in order to respond to the discourse, it is necessary to conduct research to calculate the impact of the reallocation of the fertilizer subsidy on farmers' income. The purpose of this study is to compare the impact of fertilizer subsidies and HPP rice subsidies on farmers' income. The data used in this study are primary data and secondary data. Primary data in the form of interviews or FGD with rice farmers. Secondary data can be from various related literature. The data sources for this research are farmers or farmer groups, the Central Bureau of Statistics, the Department of Agriculture, and the Ministry of Agriculture. Data analysis using PAM (Policy Analysis Matrix) method. The result of this research is that the government purchase price subsidy has a more significant impact on farmers' income than the fertilizer subsidy.Keywords: Fertilizer subsidies, HPP grain, policy analysis matrix, incomeAbstrakImplementasi program pupuk bersubsidi saat ini kurang efektif ditandai terjadinya kelangkaan pasokan dan melonjaknya harga pupuk ditingkat petani. Kondisi ini membuat pemerintah, DPR dan masyarakat relatif belum puas terhadap kebijakan subsidi pupuk saat ini sehingga menjadi wacana untuk mengganti modus subsidi pupuk yang dibayarkan langsung ke produsen menjadi subsidi langsung yang dibayarkan ke petani. Bagaimanapun harus disadari bahwa subsidi yang dibayarkan langsung kepada produsen maupun subsidi yang dibayarkan langsung ke petani akan memiliki kelebihan dan kekurangan berdasarkan faktor-faktor yang mempengaruhinya. Oleh karena itu dalam rangka merespon wacana tersebut perlu dilakukan penelitian untuk menghitung dampak realokasi subsidi pupuk tersebut pada pendapatan petani. Tujuan penelitian ini, mengetahui perbandingan dampak subsidi pupuk dan subsidi HPP gabah terhadap pendapatan petani. Data yang digunakan dalam penelitian ini adalah data primer dan data sekunder. Data primer berupa wawancara atau FGD dengan petani padi. Data sekunder di dapat dari berbagai literature yang terkait. Sumber data penelitian ini adalah petani atau kelompok tani, Badan Pusat Statistik, Dinas Pertanian dan Kementerian Pertanian. Analisis data menggunakan metode PAM (Policy Analysis Matrix. Hasil penelitian ini adalah subsidi harga pembelian pemerintah lebih berdampak signifikan terhadap pendapatan petani daripada subsidi pupuk.Kata Kunci: Subsidi pupuk, HPP gabah, Policy Analysis Matrix, pendapatan